A Systematic Review of Storytelling Strategy in Empowering Speaking Skill in EFL Classrooms - Kanar Zirak Haseeb Chicho; Ahmed Hussin Abdulla (Zanco Journal of Humanity Sciences)
Language educators aim to promote speaking skill because speaking skill is one of the productive skills that make foreign language learners create meaningful conversations and dialogues with the target language. Speaking skill is highly significant. Additionally, enhancing speaking skill requires actively involved students, and for that, language instructors need to use some tools and strategies. There are different methods and strategies for promoting speaking skill, such as story-telling strategies. Story-telling strategies aim to have communication and discussions in the class via narrating stories. Additionally, the story-telling method involves the students practicing their communication skills.  Thus, this research paper explores the values of story-telling strategies in the EFL classroom. The present study, a qualitative research design was implemented, and the data was collected from secondary sources such as research articles. For analyzing the data, a systematic analysis was implemented. Results demonstrated that story-telling was highly sufficient in improving speaking skill including teaching vocabulary. It enhances the capacity of acquiring new vocabulary, fostering pronunciation. It also enables the learner's imitation skill, expanding the learner's communication, including their criticality. In brief, story-telling strategies help language learners to improve their speaking skill. Classroom.